Role of Supervisor Support in Promoting Mental Health at the Workplace - Nuri Purwito Adi; Kiminori Odagami; Tomohisa Nagata (The Indonesian Journal of Community and Occupational Medicine, 2022)
World mental health day is celebrated on October 10th annually. This year (2022) theme is “make mental health and wellbeing for all a global priority”.1 Mental health problem is one of the emerging health problems in the world. World Health Organization (WHO) stated that estimated 15% of working-age adults have a mental disorder at any point in time. Japan reported increasing number of mental health problem registered to the workers’ compensation in 2021. The number is keep increasing each year.2 The problem is existed not only in developed country but also in the developing country. Data of Basic Health Research of Indonesia mentioned mental health problem was suffered by more than six percent of population in reproductive ages and about 19% of Indonesian youth have had suicidal thought.3 Mental health is defined as a state of mental wellbeing that enables people to cope with the stress’s life, to realize their ability, to learn well and work well, and to contribute to their communities. Poor mental health will lead to a negative impact on cognitive, behavioral, emotional, social, relational wellbeing and functioning, physical health, and personal identity and wellbeing related to work.4 Mental health problem is directly related with certain caused that usually identify as stressor or psychosocial factor. Stressors are existed at the workplaces and responsible for some mental health problems among workers. Since the caused may exist in the workplace, a proper promotion in the workplace to reduce or eliminate the impacts is necessary. In occupational health setting, the current concepts widely developed and implemented to draw the condition related to burnout, mental health and work performance is job-demand resource model. Job demand-resource model draw the balance of “demand”, which play as a negative side, and “resource”, which play as a positive side. If the balance is good and resources are much than demands, workers wellbeing are good. Job demands are similar with stressor or psychosocial factors at the workplace, it may identify more detail such as: quantitative and qualitative workloads, role ambiguity, emotional demands and others. While resources are factors in the workplace that reduce the demands, enhance productivity and achieving work goal.5 Tummers et al concluded that leadership can affect demand and resources balance in some routes. Leadership can directly affect demands and resources. When leader provide motivation, support and autonomy, it will lead to improving job resources, while a bad leader may become anger, irritable, and perform harassment that increase demands. These conditions might directly alter demands and resources among employees. Leadership can also moderate link between resources and motivation and the link between demands and strain. Within job demand-resources model, a good job resources condition will lead to good motivation among employees and in the opposite, too much job demands will lead to job strain, mental stress and some other physical health complaints. Leaders can stimulate employee to use their resources to become more proactive and lead to better engagement with their work or modify workload to reduce demands toward better physical and mental conditions.6 Therefore, in those cases, leader might moderate the link between resources and motivation as well as demands and strain and acts positively to promote attitude of employees related with motivation such as work engagement or modify job demands in order to minimize strain and mental stress so employee will keep being healthy. Van Hees et al confirmed that supervisor may play important role in supporting employee with mental health issues. Their intervention study concluded that supervisor can be guided to take a role in maintaining good environment for employee and resulted improvement in the mental health problem.7 In the other hand, supervisor need to be supported by the organization or the employer. Shanock et al stated that in order for supervisors to be able to provide appropriate support, the organization needs to provide support to the supervisors themselves.8 Supervisor usually plays many roles and keep busy with their duties and responsible. As an executive, supervisors must perceive that they receive a proper support from their directors or company’s owner so that they can act properly as a good supervisor. We might conclude that either declare as a leader or supervisor, supervisor play important role in creating proper environment to ensure positive resources and reduce demands at the workplace. In more practical ways, supervisor can act to boost positive resource by maintaining good communication, support and coaching to the employee and reduce demands by regularly monitor workload, emotional demands, and organizational flow. This action will maintain the balance of demands and resources, create creativity of the employee, increase job crafting, reduce self-undermining and lead to better health status, work engagement and productivity. But supervisor need to be supported by their supra-ordinates in order to act properly. Therefore, support from both, supervisors and the directors or owners are very important and need to be prioritized in the workplace to promote mental health and wellbeing of the employee. And by doing it, we’re also echoing our mental health day theme this year (2022) through our communities.